Amine-functionalized Cu-MOF nanospheres towards label-free hepatitis B surface antigen electrochemical immunosensors. Issue 28 (5th July 2021) - Rezki, Muhammad; Septiani, Ni Luh Wulan; Iqbal, Muhammad; Harimurti, Suksmandhira; Sambegoro, Poetro; Adhika, Damar Rastri; Yuliarto, Brian
Abstract : Label-free hepatitis B surface antigen electrochemical immunosensors by Cu-NH2 BDC MOFs. Abstract : Metal–organic framework (MOF) nanomaterials offer a wide range of promising applications due to their unique properties, including open micro- and mesopores and richness of functionalization. Herein, a facile synthesis via a solvothermal method was successfully employed to prepare amine-functionalized Cu-MOF nanospheres. Moreover, the growth and the morphology of the nanospheres were optimized by the addition of PVP and TEA. By functionalization with an amine group, the immobilization of a bioreceptor towards the detection of hepatitis B infection biomarker, i.e., hepatitis B surface antigen (HBsAg), could be realized. The immobilization of the bioreceptor/antibody to Cu-MOF nanospheres was achieved through a covalent interaction between the carboxyl group of the antibodies and the amino-functional ligand in Cu-MOF via EDC/NHS coupling. The amine-functionalized Cu-MOF nanospheres act not only as a nanocarrier for antibody immobilization, but also as an electroactive material to generate the electrochemical signal. The electrochemical sensing performance was characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV). The results showed that the current response proportionally decreased with the increase of HBsAg concentration. More importantly, the sensing performance of the amine-functionalized Cu-MOF nanospheres towards HBsAg detection was found to be consistent in real human serum media. This strategy successfully resulted in wide linear range detection of HBsAg from 1 ng mL −1 to 500 ng mL −1 with a limit of detection (LOD) of 730 pg mL −1 . Thus, our approach provides a facile and low-cost synthesis process of an electrochemical immunosensor and paves the way to potentially utilize MOF-based nanomaterials for clinical use.